Relationship between NDVI of Patches and Cover Area of Grasses, Shrubs and Bare Soil Components of a Semi-Arid Steppe from North-West Patagonia, Argentina - Farina, Clara Maria (2023)
Distinguishing the contributions of different vegetation cover such as shrubs and grasses components into the primary production in arid and semi-arid rangelands is a key step to understanding changes at a landscape scale. The aim was to assess the contribution of shrubs, grasses and bare soil components into a total biophysical variable at a patch level, and the relationship between that biophysical variable and remote sensing vegetation index, in a grass–shrub steppe from North-West Patagonia, Argentina. We conducted a field survey in the period 2015–2017 to analyzing the relationship between monthly values of Normalized Difference Vegetation Index (NDVI) of two grasses, two shrub species and bare soil, weighted by their cover area at a patch level, and the concomitant patch NDVI records, respectively. The contribution of the patch components to the total NDVI value at a patch level was additive. The relationship between the weighted NDVI of patch components and the concomitant NDVI value at a patch level along time was linear for perennial grasses and deciduous shrub–grass patches, but linearity was not significant for most perennial shrub–grass patches. Differences among patch compositions and their surface reflectance suggest the need to move forward in a more precise distinction of the floristic composition of patches, to better understanding their contribution to NDVI temporal dynamics at a landscape scale.